An unknown view of Mt. Zion monastery by the Flemish old master Pieter Coecke van Aelst (1502-1550) as evidence to his pilgrimage to Jerusalem - Lewy, M. (Liber Annuus, 2005)
Abstract Master Pieter Coecke van Aelst executed the ink drawing which is now released from its anonymity. Furthermore, it has been proven that he made a pilgrimage to Jerusalem during the year 1533 or 1534. He can therefore be included in the list of the only few Old Masters who sighted the Holy Land with their own eyes in the 16th century. Moreover, he was one of the last pilgrim artists who could still witness the presence of the friars on Mt. Zion. It remains to be seen under what circumstances Hermann Borculus prepared his woodcut of Jerusalem in 1538 (see figure 9), in which Mt. Zion appears as well. As long as we are not sure about his own visit to Jerusalem, we were still puzzling who could have been possibly Borculusʼ source of inspiration.